Exploring the Potential of Araceae Plants in Penggaron Forest for Traditional Medicine and Biodiversity Conservation - Baiq Farhatul Wahidah; Fadly Husain; Rizkiati Khasanah (Jurnal Ilmu Lingkungan, 2026)
Penggaron Forest possesses high biodiversity; however, information regarding the interconnectedness between Araceae diversity, phytochemical constituents, and their potential utilization as a source of traditional medicine within the framework of ecosystem conservation remains highly limited. This study aims to fill this gap by documenting Araceae diversity, analyzing phytochemical constituents, and evaluating their ecological roles along with their utilization by local communities. This objective was achieved through an integrated approach that synthesizes taxonomic inventory, laboratory screening, and the exploration of traditional knowledge to map the potential of this aroid group within bioresource-based conservation programs. The methods employed include plant sampling, species identification, phytochemical analysis, and interviews with the local community. A total of ten Araceae species were successfully identified. Laboratory analyses confirmed a universal accumulation of primary bioactive compounds, namely alkaloids and flavonoids, across all tested species specimens. Furthermore, variations in the distribution of supporting secondary metabolites—including tannins, saponins, phenolics, and terpenoids—were detected, which biochemically exhibit strong potentials as natural anti-inflammatory, antimicrobial, and antioxidant agents. Several species also contribute to ecosystem conservation through erosion control, microhabitat provisioning, and maintaining soil stability. Ethnobotanically, a distinct knowledge gap persists among the local community, whose utilization remains lopsidedly focused on external ornamental plant trading and rudimentary food preparation, completely leaving the therapeutic values of local wild aroids unrecognized. These findings demonstrate that the Araceae group in Penggaron Forest possesses strategic potential as a source of alternative biopharmaceuticals while simultaneously serving as a sensitive bioindicator to support understory biodiversity preservation, thereby warranting further development as a sustainable biological resource asset.